Arabic Techno-Paper Poetry: Creative Justifications And Literary Features/ الشعر التكنو ورقي: المُسوّغات الإبداعيَّة والسّمات الأدبيَّة - Hiba Mohammed Mhidi; Harith Yaseen Shukur (Ijaz Arabi Journal of Arabic Learning, 2026)
This study seeks to uncover the most important creative justifications and literary characteristics of "techno-paper" poetry, as a new and emerging creative activity on the surface of Arabic literature, emerging as a reaction to the extremist calls for adopters of both the digital and paper mediums. It also examines the most important literary characteristics and features that distinguish this new literary genre from other literary genres. The study relied on the data of the descriptive approach, which includes monitoring the phenomenon and attempting to analyze it in order to reach the desired goal of this study. The study found that techno-paper poetry is a literary genre that combines two worlds that have always been described as contradictory, and that it thus provides a rich and fertile environment for the reader, as it combines many tools of expression that have come from these two worlds (paper and digital), such as words, sound, images, movement, etc., which makes it a unique poetic discourse that combines both discourses and transcends them at the same time. The study concluded that techno-paper poetry does not abolish paper or digital poetry, but rather attempts to bridge the gap and overcome the fanaticism of each. It serves as a vivid and brilliant example of the clash between literature and technology, satisfy two competing requirements by attempting to curb the fanaticism of both groups emphasizing that belief in the implications or outcomes of technology does not necessarily lead to the demise of print literature and a decline in its value.